BEYOND NUTRITION: INTEGRATING EDUCATIONAL PSYCHOLOGY, INCLUSIVE EDUCATION, AND NURSING PERSPECTIVES ON FEEDING CHALLENGES IN CHILDREN WITH AUTISM - Wijayaningsih, Lanny; Widiastuti, Ajeng A; Kriswandani; Indarini, Endang; Eryani, Salwa A (NurseLine Journal, 2026)
ABSTRACT Background: Feeding difficulties are among the most prevalent challenges experienced by children with autism spectrum disorder (ASD), often manifesting in sensory sensitivities, food selectivity, rapid eating, and emotional reactivity during mealtimes. While previous studies have predominantly emphasized clinical and therapeutic approaches, the intersection of feeding behaviors with educational and nursing perspectives remains underexplored. Objectives: This study aimed to explore the patterns of feeding difficulties in children with autism and to examine their implications for educational and nursing practices. Methods: A qualitative descriptive design was employed, involving seven parents of children with autism. Data were collected through structured questionnaires and in-depth interviews, enabling the integration of observable feeding behaviors with parental experiences. Results: The findings revealed that sensory sensitivity and selective eating were the most dominant challenges, leading to restricted food repertoires and nutritional risks. Rapid eating behaviors raised concerns for digestion, nutrient absorption, and choking hazards. Emotional responses to food varied across children, ranging from minimal distress to significant tantrums, underscoring the heterogeneous nature of feeding difficulties. These challenges intersect with self-regulation, executive functioning, and socio-emotional adjustment, thereby influencing children’s readiness to learn and classroom participation. Conclusion: Feeding difficulties in children with autism are multidimensional, affecting nutritional health, learning readiness, and socio-emotional development. The study highlights the need to integrate educational psychology, inclusive education, and nursing perspectives in addressing feeding-related challenges. School nurses play a pivotal role in early detection, health education, and interdisciplinary collaboration with teachers and parents to create inclusive and supportive mealtime routines, ultimately improving both educational outcomes and quality of life for children with autism. Keywords: Autism Spectrum Disorder; Feeding Difficulties; Inclusive Education; School Nursing; Educational Psychology